Transaksi Alat Kesehatan Secara Elektronik Di Marketplace - Sandjaja, Arif; Saleh, Mohammad (Dinasti Review Publisher, 2024)
This article aims to specifically examine Electronic Medical Device Transactions in the Marketplace. As is known, since the Covid-19 pandemic, the value of transactions via the internet network has increased rapidly, due to a shift in consumer spending patterns from face-to-face transactions to online transactions. Even now, after the end of the Covid-19 pandemic, the habit of shopping online has become a new habit, including for medical equipment products which basically have their own regulations regarding conventional distribution. Apart from that, it is necessary to study various laws and regulations related to the distribution of medical devices in Indonesia, reveal gaps in administrative law, and it is hoped that this can contribute to ideas so that the interests of the wider community are protected.